Compliance With Preferred Reporting Items for Systematic Review and Meta-Analysis Individual Participant Data Statement for Meta-Analyses Published for Stroke Studies. Issue 9 (September 2021) - Jumah, Fareed; Chotai, Silky; Ashraf, Omar; Rallo, Michael S.; Raju, Bharath; Gadhiya, Arjun; Sun, Hai; Narayan, Vinayak; Gupta, Gaurav; Nanda, Anil
Abstract : Background and Purpose: Individual-participant data meta-analyses (IPD-MA) are powerful evidence synthesis studies which are considered the gold-standard of MA. The quality of reporting in these studies is guided by the 2015 Preferred Reporting Items for Systematic Review and Meta-Analysis of Individual Participant Data (PRISMA-IPD) guidelines. The growing number of IPD-MA published for stroke studies calls for an assessment of the compliance of these studies with the PRISMA-IPD statement. Methods: PubMed and EMBASE were searched for MA in stroke published between January 1, 2016, and March 30, 2020, in journals with impact factor >2. Literature reviews, scoping reviews, and aggregate MA were excluded. The final articles were scored using the 31-item PRISMA-IPD checklist. Results were depicted using descriptive statistics. Compliance with each item in PRISM-IPD guideline was recorded. The study was defined as compliant to IPD analyses if it satisfied all IPD specific items. Results: From an initial set of 321 articles, 31 met the final eligibility for data extraction. Only 4 (13%) described the use of PRISMA-IPD guidelines in their methodology, while 8/31 (26%) used the old PRISMA guidelines and 19/31 (61%) followed none. Regardless of mention of using IPD specific guidelines, 42% (n=13) of studies were compliant with all 4 IPD specific domains. The poorest areas of compliance were bias assessment within (32%) and across (39%) studies, reporting protocol and registration (42%), and reporting of IPD integrity (48%). The median journal impact factor was similar between the compliant (median, 8.1 [interquartile range, 5.4–39.9]) and noncompliant (median, 6 [interquartile range, 4.5–16.2]) groups ( P =0.24). Similarly, the journal, country of correspondence, number of authors, number of studies included in MA, study sample size, and funding source were statistically similar between the groups. Conclusions: For the published IPD-MA stroke studies, the compliance with PRISMA-IPD statement and compliance with 4 IPD specific items was suboptimal. The journal, author, and study-related factors were not associated with compliance. Additional scrutiny measures to ensure adherence to mandated guidelines might increase the compliance. Several avenues to improve compliance and ensure optimal adherence are discussed. Abstract : Supplemental Digital Content is available in the text.